11x=8x+6

Simple and best practice solution for 11x=8x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x=8x+6 equation:


Simplifying
11x = 8x + 6

Reorder the terms:
11x = 6 + 8x

Solving
11x = 6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
11x + -8x = 6 + 8x + -8x

Combine like terms: 11x + -8x = 3x
3x = 6 + 8x + -8x

Combine like terms: 8x + -8x = 0
3x = 6 + 0
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| M-(-5)=19 | | -11=11(r-3) | | 5y+9(3y+2)=274 | | 5(10x-4)-3x-7=13x-20 | | 5x-10+3x+20=180 | | r+6+4=10 | | 18s-17-7s=16+8s | | 3x+2+x=5x+5 | | .66x+4=.6-2 | | 230+.15x=369.50 | | 2x+57=5x | | 3a+1=3.6(1a-1) | | 5+3h=4h | | x-(1-2x)= | | -7-5n=28 | | 32+4(c-1)=(4c+5) | | 9x^2-10.5x-73.5=0 | | 9t+20=19t-6t-20 | | 28-0.3y=0.7y | | 7(r-7)=-49 | | 7(7x+9)=49x-10 | | -6x+6x+14=14 | | 9m-14= | | x*.10=x*.15 | | 14-3n=26 | | 8c+5(c-3)= | | x^3-3x^2+9x-27=0 | | 5x-30=40+3x | | 2x+7=2x-4 | | 8c+(5c-3)= | | 5b+4=2(b+2) | | 9k-19-8k=-2k+11 |

Equations solver categories